Regulation of Intestinal Inflammation by Dietary Fats - Basson, Abigail R.; Chen, Christy; Sagl, Filip; Trotter, Ashley; Bederman, Ilya; Gomez-Nguyen, Adrian; Sundrud, Mark S.; Ilic, Sanja; Cominelli, Fabio; Rodriguez-Palacios, Alex (Frontiers in Immunology, 2021)
With the epidemic of human obesity, dietary fats have been extensively studied since epidemiological studies indicate that high-fat diets (HFDs), especially those rich in long-chain saturated fatty acids (e.g., Western Diet, National Health Examination survey; NHANES ‘What We Eat in America’ report) have multi-organ pro-inflammatory effects. Experimental studies have confirmed such an association and have roughly defined mechanisms linked to disease induction. However, the observed effects from epidemiological studies appear to be an over-simplification of the mechanistic complexity that depends on the host, the dietary fatty acid, and the rather personalized genetics and variability of the gut microbiota. Of interest, experimental studies have shown that certain saturated fats (e.g., lauric and myristic fatty acid-rich coconut oil) could exert the opposite effect; that is, desirable anti-inflammatory and protective mechanisms promoting gut health by unanticipated pathways. Owing to the experimental advantages of laboratory animals for the study of mechanisms under well-controlled dietary settings, herein we focused on summarizing our current understanding on the role of dietary fatty acids on intestinal biology, namely in mice and rats, with validation in cell systems or human studies. Herein, we provide a scoping overview of the most studied mechanisms of disease associated with disease induction or prevention of Inflammatory Bowel Disease rodent models relevant Crohn’s Disease and Ulcerative Colitis after feeding either the bulk food HFD or the target-fatty acid/or dietary molecule. We also provide a general outlook on areas that have been largely or scarcely studied, primarily, assessing the effect of HFD in controlling acute and chronic forms of intestinal inflammation.